Nutritional Value of Banded Cricket and Mealworm Larvae - Jagoda Kępińska-Pacelik; Wioletta Biel; Cezary Podsiadło; Grzegorz Tokarczyk; Patrycja Biernacka; Grzegorz Bienkiewicz (Foods, 2023)
Insect farming is more ecological than traditional animal farming, as it requires less water and contributes to lower greenhouse gas emissions. In our study, banded cricket (BC) and mealworm larvae (ML) were analyzed. The proximate composition was determined according to Association of Official Analytical Chemists. The mineral content was determined by colorimetry and mass spectrometry. Fatty acid methyl esters (FAMEs) were obtained from the samples and separated using a gas chromatography apparatus, coupled with a mass spectrometer. Our research confirmed that insects are a rich source of protein, with ML containing significantly more protein than BC (74.41 and 65.66 g/100 g dry matter (DM), respectively). In terms of the content of macrominerals, ML was significantly richer than BC, especially in terms of magnesium content (8.75 g/100 g DM). In terms of the content of saturated fatty acids, BC contained almost twice as much as ML (40.05 and 24.74% of the sum of fatty acids, respectively). EPA and DHA were only detected in the fat of BC. The presented results prove that both ML and BC can be good sources of protein both in human and companion animal diets. The component that is predominantly high in insects is fat, with a favorable fatty acid profile, especially in terms of polyunsaturated fatty acids. This study contributes new knowledge on the nutritional value of edible insects. In this research, we included three different nitrogen conversion factors for crude protein content. Our results partially confirm previous studies by other authors, although they provide new information on the content of fatty acids.